Oligosoma eludens sp. nov. (Reptilia: Scincidae) from the Hawkdun, Ida, and Saint Bathans Ranges of North Otago, Aotearoa/New Zealand - Knox, Carey; Chapple, David G.; Bell, Trent (Zootaxa, 2024)
A species of diurnal skink from the Hawkdun, Ida, and Saint Bathans Ranges of North Otago, Aotearoa/New Zealand is described as Oligosoma eludens sp. nov. It is a small species, coloured mid- to dark brown with especially fine, smooth longitudinal stripes, and lives along the edges of greywacke screes in alpine grasslands. This skink is cryptic, fast moving, and displays erratic emergence, generally only being easily detectable in the early morning or evening.